2001
DOI: 10.3758/bf03194472
|View full text |Cite
|
Sign up to set email alerts
|

The midstream order deficit

Abstract: Warren, Obusek, Farmer, and Warren (1969) reported a striking inability of listeners to perceive the relative order of a sequence of four sounds presented repeatedly, despite their fairly accurate performance when the sequence was presented only once. Their participants first heard the four sounds separately and learned a name for each. Then they were told that the four sounds would be presented in a particular order repeatedly and that afterwards they would be asked to report the correct relative order. A cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…The results showed that correct identiWcations for earlier target positions (the Wrst and second Bins) were lower, and were consistently higher after the third Bin. This Wnding is consistent with the hypothesis based on attentional preparation, or the initiating act suggested by Holcombe et al (2001). In the beginning of the RSVP sequence, the observers would begin attentional preparation to eYciently process a target that might appear anytime.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The results showed that correct identiWcations for earlier target positions (the Wrst and second Bins) were lower, and were consistently higher after the third Bin. This Wnding is consistent with the hypothesis based on attentional preparation, or the initiating act suggested by Holcombe et al (2001). In the beginning of the RSVP sequence, the observers would begin attentional preparation to eYciently process a target that might appear anytime.…”
Section: Resultssupporting
confidence: 78%
“…In all the experiments, there was a transient deWcit in identifying a target presented at the very beginning of the RSVP sequence. This deWcit in the identiWcation of the target could be the cost of the process of orienting temporal attention, the attentional preparation, which is consistent with the implication of Holcombe et al (2001). The attentional preparation process in the Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…No, because unlike in our ring condition, with only a half-cycle stimulus snippet presented, a color-motion asynchrony is still found, as previously reported by Linares and López-Moliner (2006) and as found in a pilot experiment we conducted using the stimulus parameters of this experiment (data not shown). Our ring condition also differs from presentation of only a half-cycle in that a half-cycle presentation introduces temporal order cues including visual persistence and onset cues that do not occur in a longer stream (Beaudot, 2002;Dakin & Bex, 2002;Holcombe, Kanwisher, & Treisman, 2001) even when the longer stream is exogenously cued (Holcombe, Kanwisher, & Treisman, unpublished observation).…”
Section: Features Accessed Independently Rather Than Together-mentioning
confidence: 99%